HUBUNGAN ASPEK SOKONGAN SOSIAL DAN KEMURUNGAN DALAM KALANGAN PELAJAR - Mohd Nor Azlan, Nur Shahirah; Yahya, Siti Aishah (Jurnal ’Ulwan, 2023)
The Covid-19 outbreak in Malaysia brings a huge impact on the country including towards the education sector. Amidst the issues that arise are lack of social support and mental health problems such as depression among school students during the pandemic. Hence, the objective of this study is to identify the relationship between these aspects which are social support and depression. This survey had been conducted towards 113 students consisting 37 form one students, 38 form two students and 38 form three students from Sekolah Menengah Kebangsaan Datuk Muhammad Yusof by handing out questionnaire. The questionnaire used includes the Inventory of Social Support Behavior (ISSB) and the Beck Depression Inventory (BDI). The data obtained through this study was analyzed via quantitative analysis using the Statistical Package for Social Science (SPSS) version 25.0. The result of the study shows that there is a significant relationship between social support and depression [r = -4.446, p